Concept verification of a Remote Automatic Scoring System for Evaluating Knee Function after Total Knee Arthroplasty - Zhang, Haohua; Zhou, Yixin (The Journal of Knee Surgery, 2020)
The Knee Society Score (KSS) is the most commonly used scale for evaluating postoperative pain and physical function after total knee arthroplasty (TKA). However, this scale requires clinic visiting, which is not quite convenient. Our concept verification study demonstrated a remote automatic system for evaluating knee function after TKA using the KSS. The remote scoring system consists of two modules for data acquisition, an application for patients, a cloud server, and an application for doctors. The kinematic data are collected by the data acquisition modules and transmitted to the patient application via Bluetooth. The data acquisition module contains a motion sensor, a microcontroller unit, a power supply, and a Bluetooth module. The motion sensor consists of an accelerometer, a gyroscope, and a geomagnetic sensor, all of which are three-axis instruments. Using the nine-axis data, the three-dimensional (3D) angles are calculated according to the theory of attitude and heading reference system. The KSS score is calculated using a scoring algorithm in the patient application and transmitted to the doctor application through the cloud server. The knee function of 10 patients treated with unilateral TKA was evaluated by both a doctor and the remote scoring system. The consistency in KSS between the doctor and the system was analyzed using the paired t-test. The remote scoring system successfully recorded knee function data and transmitted the scores from the patient application to the doctor application through the cloud server. There was no significant difference in the KSS scores evaluated by the doctor and that by the system (p = 0.326). This remote automatic scoring system provides a reliable and convenient method for evaluating knee function after TKA at home.
Keywords: knee society score; total knee arthroplasty; remote automatic scoring system